2016
DOI: 10.1186/s40733-016-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of asthma in young children: evidence-based recommendations

Abstract: In the present review, we focus on evidence-based data for the use of inhaled corticosteroids (ICS), leukotriene receptor antagonist (LTRA), long-acting beta2-agonits (LABA) and oral corticosteroids (OCS), with a special emphasis on well-performed randomized clinical trials (RCTs) and meta-analyses of such trials for the chronic management of asthma/wheeze in infants and preschoolers. Results: Seven meta-analyses and 14 RCTs were reviewed. Daily ICS should be the preferred drug for infants/preschoolers with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
24
0
3
Order By: Relevance
“…45 In 2015, Ducharme et al 13 published a nonsystematic review of preschool wheeze with meta-analyses of newer studies; they reported similar results comparing daily ICS with placebo (relative risk 0.57; 95% CI, 0.40-0.80) and daily and intermittent ICS (relative risk 0.91; 95% CI, 0.71-1.18). The conclusions of a 2016 nonsystematic review by CastroRodriguez et al 46 were also in line with our findings.…”
Section: Figuresupporting
confidence: 92%
“…45 In 2015, Ducharme et al 13 published a nonsystematic review of preschool wheeze with meta-analyses of newer studies; they reported similar results comparing daily ICS with placebo (relative risk 0.57; 95% CI, 0.40-0.80) and daily and intermittent ICS (relative risk 0.91; 95% CI, 0.71-1.18). The conclusions of a 2016 nonsystematic review by CastroRodriguez et al 46 were also in line with our findings.…”
Section: Figuresupporting
confidence: 92%
“…Therefore, additional studies at a low‐risk of bias are clearly warranted to compare the efficacy of ICS versus montelukast in preschoolers with asthma or recurrent wheezing. Parallel‐group trials with standardized reporting of outcomes would allow better quantification of the magnitude of effect for various efficacy and safety outcomes and more cross‐over trials are needed to establish solid evidence‐based criteria on which to personalize the initial choice of monotherapy . It is particularly crucial to establish the best controller therapy in this young age group as asthmatic preschoolers have the highest morbidity, experiencing more exacerbations requiring SC and hospital admissions than other all other pediatric age groups, with many exhibiting irreversible lung function impairment by 6 years of age .…”
Section: Discussionmentioning
confidence: 99%
“…Un metaanálisis reciente evidenció que la terapia con CI inhalados debe preferirse sobre otros medicamentos (antagonistas de los leucotrienos, β-adrenérgicos de acción prolongada y corticoides orales) y que su utilización diaria es mejor que la intermitente para disminuir los síntomas respiratorios cotidianos (50).…”
Section: Las Ventajas Del Tratamiento Tempranounclassified